The Evaluation Simulator: A New Approach to Training Music Performance Assessment - Waddell, George; Perkins, Rosie; Williamon, Aaron (Frontiers in Psychology, 2019)
A growing body of work has examined the act of evaluating the quality of a musical performance. The present paper identifies a methodological gap where a new approach could allow for enhanced study of the evaluative environment in a an experimentally-controlled setting. It then considers the parallel domain of training evaluative skills in musicians, presenting assessment as a form of performance to be taught and demonstrating a similar gap in opportunities for trainees to develop evaluative skills within the heightened environments of live assessment scenarios. To address these parallel needs, the concepts of Immersive Virtual Environments (IVEs) and distributed simulation are outlined, highlighting their use in training and research other performance domains. Taking this model as a starting point, the paper presents the development of the Evaluation Simulator as a new tool to study and train performance evaluation. Potential applications of this technology in academic and pedagogical settings are then discussed.